Acute joint inflammation alters the adrenoceptor profile of synovial blood vessels in the knee joints of rabbits. Issue 10 (October 1992) - Gray, E; Ferrell, W R
Abstract : Experiments were carried out to examine the effect of acute inflammation, induced by intra-articular injection of 2% carrageenan, on the response of articular blood vessels in the knee joints of rabbits to adrenoceptor agonists. The responses to noradrenaline, phenylephrine, clonidine, UK-14304, and isoprenaline were examined 24 hours after carrageenan injection and compared with those of normal animals. Antagonists specific for alpha 1 and alpha 2 were used to identify the adrenoceptors through which the responses were mediated and to examine if carrageenan treatment altered the adrenoceptor profile of these blood vessels. The evidence suggests that in the carrageenan treated animals there is a reduction in the alpha 1 response with an associated increase in the alpha 2 response. A decrease in the number or affinity of alpha 1 adrenoceptors is indicated by the shift to the right of the noradrenaline and phenylephrine dose/response curves, whereas an increase in alpha 2 affinity or number is suggested by the associated leftward shift in the alpha 2 adrenoceptor agonist curves. This change in receptor profile appears to arise as a direct result of carrageenan induced joint inflammation.